Review on degradation mechanism and health state estimation methods of lithium-ion batteries - Yongtao Liu; Chuanpan Liu; Yongjie Liu; Feiran Sun; Jie Qiao; Ting Xu (Journal of Traffic and Transportation Engineering (English ed. Online), 2023)
State of health (SOH) estimation is important for a lithium-ion battery (LIB) health state management system, and accurate estimation of SOH is influenced by the degree of degradation of the LIB. However, considering the complex electrochemical reactions within Li electrons and the influence of many external factors on internal reactions, it is difficult to accurately estimate the SOH based on the surface state characteristics of the battery (including current, voltage, and temperature). Thus, in this study, the knowledge graph method is employed to analyze keyword co-occurrences and citations in the literature on LIB degradation and SOH estimation to determine research hotspots. Based on the research trends, findings regarding the internal and external degradation mechanisms and influencing factors of (LIBs) are reorganized, and chemical and physical degradation processes, including solid electrolyte interface (SEI) layer formation, fracture, Li plating, and dendrite formation, are systematically introduced based on the modeling perspective. The interrelationships between these degradation factors and their effects on capacity and power decay as well as their correlation with SOH estimation are evaluated. Additionally, a comparative analysis of existing SOH estimation methods is presented, and the applicable scenarios and technical problems of each method are summarized. The key issues such as model simplification, estimation methods based on random data, and second-life SOH are also analyzed and discussed. The results show that the estimation results of methods mixing multiple models tend to be more accurate. Finally, the development trend of SOH estimation methods under complex degradation conditions and usage scenarios is analytically discussed.